PERAN DINAS TENAGA KERJA, PERINDUSTRIAN, KOPERASI DAN UKM DALAM PEMBERDAYAAN UMKM SENTRA TAS DI DESA LORAM KULON KECAMATAN JATI KABUPATEN KUDUS - Dian Ratika Yuniasari; Achmad Taufiq; Nunik Retno Herawati (Journal of Politic and Government Studies, 2018)
Micro Small and Medium Enterprises (MSMEs) is one of the prime powers of economic activity in Indonesia. The contribution of the MSME sector to Gross Domestic Product increased from 57.84 percent to 60.34 percent in 2017. By seeing the magnitude of the influence of SMEs, the role of government in the empowerment of SMEs is necessary so that business can still exist and survive in the economic flow. Kudus is the smallest district in Central Java, but the industry in the district is also growing quite rapidly. The industrial sector became the main pillar of the economy of Kudus district with a contribution of 81.09 percent. One of the main buffers of the economy is the sector of MSME where in Kudus there are many SMEs from various sectors such as border, batik, bag, knife and food. Loram Kulon Village as one of the centers of bags also requires the role of government in the empowerment of SMEs. One part of government that has a role in the empowerment of SMEs is the Department of Labor, Industry, Cooperatives and SMEs.This study aims to determine the role of the Department of Labor, Industry, Cooperatives and SMEs in the empowerment of bag business in West Loram Village. In addition, this study also aims to determine the supporting factors and inhibiting factors in the effort of empowerment. This research uses descriptive qualitative method with observation, interview and documentation techniques.            The results of this study indicate that the role of the Department of Labor, Industry, Cooperatives and SMEs in the empowerment of bag business in West Loram Village as a bag-making center has not run optimally. This happens because from the official itself there has been no specific agenda for the village. In addition, one of the factors that become obstacles in empowerment efforts is the absence of organizations or associations that become a container for business players. It is because the bag from the community itself is also difficult to be invited to organize so that the government also has difficulty to channel assistance.Keywords: Role of Government, Empowerment, MSME